2019
DOI: 10.3389/fpsyg.2019.00542
|View full text |Cite
|
Sign up to set email alerts
|

The Parent-Adolescent Relationship and Risk-Taking Behaviors Among Chinese Adolescents: The Moderating Role of Self-Control

Abstract: The present study primarily aimed to examine whether self-control serves as a moderator in the associations between parent-adolescent relationships, including parental support and parent-adolescent conflict, and risk-taking behaviors among adolescents. The 917 Chinese adolescents whose mean age was 14.38 years (SD = 1.69) completed questionnaires effectively. The results indicated that the relationships between either parental support or parent-adolescent conflict and adolescent risk-taking behavior were moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 64 publications
3
31
0
3
Order By: Relevance
“…Additionally, sleep less than 6 hours/day, study more than 8 hours/day, and higher quantity of homework were positively associated with anxiety among adolescents with depression. Long hours of studying might indicate heavy burdens of homework and insufficient sleep, which had negative impacts on the mental health of students and parent-adolescent relationships ( Boers et al, 2019 ; Brown et al, 2018 ; Liu et al, 2020b ; Liu et al, 2019 ; McMakin and Alfano, 2015 ; Stiglic and Viner, 2019 ; Sun et al, 2012 ). In line with previous study ( Zhou et al, 2020 ), female adolescents were more likely to have anxiety and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sleep less than 6 hours/day, study more than 8 hours/day, and higher quantity of homework were positively associated with anxiety among adolescents with depression. Long hours of studying might indicate heavy burdens of homework and insufficient sleep, which had negative impacts on the mental health of students and parent-adolescent relationships ( Boers et al, 2019 ; Brown et al, 2018 ; Liu et al, 2020b ; Liu et al, 2019 ; McMakin and Alfano, 2015 ; Stiglic and Viner, 2019 ; Sun et al, 2012 ). In line with previous study ( Zhou et al, 2020 ), female adolescents were more likely to have anxiety and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A study from China also found that parental orders and reprimands negatively correlated with adolescent self-esteem and emotional balance, and positively related to social anxiety and behavior problems. 16 In addition, mothers of daughters with high social anxiety tend to control and assist their daughters in their daily lives and learning. Furthermore, fathers of children with high anxiety show more controlling behavior 17 .…”
Section: Resultsmentioning
confidence: 99%
“…A close look at the literature shows that adolescents have reported the need for emotional support as one of the basic needs for maintaining their health [18]. Parents' close and intimate relationship with adolescents leads to their high social-psychological adjustment and attainment of positive identity, reduces depression and high-risk behaviors in them, and is an effective factor in reducing the effects of peers' negative inductions [18,20,21]. Effective interaction with adolescents is one of the parenting skills that has been emphasized in optimal parenting styles.…”
Section: Discussionmentioning
confidence: 99%